Parallelism Of Heaven in Al-Qur'an Translation of Kemenag and Al-Kitab Translation Of Sabda - Khairunnisa; Irfansyah (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2023)
This study discusses the parallels and similarities of heaven in the translation of the Ministry of Religious Affairs' al-Qur'an and al-kitab (the Bible) of Sabda. This study explains the similarity of the meaning of heaven between the two books because there are some similarities in explaining heaven. Therefore, this research uses the intertextuality approach pioneered by Julia Kristeva to see the similarities between the two holy books. The results of this research from the configuratioPARALLELISM OF HEAVEN IN AL-QUR'AN TRANSLATION OF KEMENAG AND AL-KITAB TRANSLATION OF SABDAn are more dominant to the similarity so that the parallel principle is more important in naming heaven, then also found the principle of excerpts, modifications in human disclosure, and description of heaven in the translation of al-Qur'an and al-Kitab.